Rancang Bangun Solder Menggunakan Sumber Daya Baterai DC - Faishal Azmi Al hakim; Rusman; Wendhi Yuniarto (entries, 2025)
The purpose of this research is as a technological development to encourage the need for a more practical and portable soldering iron. This research aims to design and build a soldering iron that uses battery power, so that it can be used in various locations without relying on conventional electricity sources. The design method includes the selection of main components such as heating elements, lithium-ion batteries and battery safety systems. The assembly process is carried out by considering energy efficiency, safety, and user comfort. The test results show that the battery-based solder is able to reach an optimal working temperature of 277.75 in 135 seconds and has a fairly long usage duration of 2.77 hours according to the 12V 9Ah battery capacity. This tool is considered quite effective for the needs of maintenance and repair of electronic devices in the field and facilitates user mobility.